2019
DOI: 10.24220/2318-0897v28n1a4389
|View full text |Cite
|
Sign up to set email alerts
|

The essential oil of Curcuma longa rhizomes as an antimicrobial and its composition by Gas Chromatography/Mass Spectrometry

Abstract: The essential oil's major components are zingiberene (11%), sesquiphellandrene (10%), β-turmerone (10%), and α-curcumene (5%). It proved efficient at inhibiting Staphylococcus aureus with Minimum Inhibitory Concentrations of 38.8μl/mL, Staphylococcus epidermidis (Minimum Inhibitory Concentrations of 50.0μl/mL), Escherichia coli (Minimum Inhibitory Concentrations of 44.4μl/mL), and Pseudomonas aeruginosa (Minimum Inhibitory Concentrations of 27.7μl/mL). Conclusion Despite provoking hemolysis in sheep red blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
2
4
0
1
Order By: Relevance
“…It could be due to the absence of compounds essential for antimicrobial potential. These results are in agreement with a study reported by Gon‫ח‬alves et al (2019). Essential oils of cinnamon and thyme have been reported to be effective against MRSA at the lowest concentration of 25 µL/mL (Gon‫ח‬alves et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…It could be due to the absence of compounds essential for antimicrobial potential. These results are in agreement with a study reported by Gon‫ח‬alves et al (2019). Essential oils of cinnamon and thyme have been reported to be effective against MRSA at the lowest concentration of 25 µL/mL (Gon‫ח‬alves et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…They have relatively high odor threshold values and usually lack substantial impact on flavor [ 43 ]. Besides, another differential compound with VIP 1.59 was identified as the terpene1-methyl-4-(6-methylhept-5-en-2-yl) benzene, which has the antimicrobial and antioxidant activities [ 44 ]. The loading plots between VFD and ND are shown in Figure S1B .…”
Section: Resultsmentioning
confidence: 99%
“…Turmerones still are also the predominant compounds in samples from Faisalabad (Pakistan) and Turkey [ 104 , 158 ]. In the South American continent, the essential oil isolated from rhizomes grown in Ecuador was rich in ar-turmerone (45.5%) and α-turmerone (13.4%), similar to Colombian samples, while that from Brazil was dominated by zingiberene (11%), sesquiphellandrene (10%), β-turmerone (10%) and α-curcumene (5%) [ 105 , 107 , 159 ].…”
Section: Chemical Analysis Of the Essential Oil Obtained From mentioning
confidence: 99%